STRENGTHS AND WEAKNESSES OF USING AUTHENTIC MATERIALS IN TEACHING LISTENING COMPREHENSION - Tuanany, Nurlaila (LP2M IAIN Ambon, 2019)
Abstract Listening is not a passive skill. It is an active process since it needs the interpretation of sounds into meaning. It is important for teachers to help their students to increase the students’ listening comprehension. This paper discusses the teaching listening comprehension using authentic materials. Authentic materials are the materials that have been produced by native speakers in the form of written or spoken language. There are strengths and weaknesses in applying these materials. Some of the strengths are more interesting, genuine, and motivating than non-authentic materials. On the other hand, the authentic materials are too difficult for lower level students so the teacher needs to spend more hours to apply them. Finally, in teaching listening comprehension the teacher needs to select the appropriate materials to meet the students’ level and knowledge background and most of all it must be suitable with the syllabus of teaching objectives. Keywords: Authentic Materials, Strengths, Weaknesses, Listening Comprehension Abstract Mendengarkan bukanlah keterampilan pasif. Mendengarkan merupakan proses aktif karena membutuhkan interpretasi suara menjadi makna. Penting bagi guru untuk membantu para siswa dalam meningkatkan kemampuan mendengarkan mereka. Tulisan ini membahas penggunaan materi otentik dalam pengajaran kemampuan mendengarkan siswa. Materi otentik adalah materi yang telah diproduksi oleh penutur asli dalam bentuk bahasa tertulis maupun lisan. Ada kelebihan dan kekurangan dalam mengaplikasikan materi ini. Beberapa kelebihan di antaranya materi otentik ini lebih menarik, asli, dan memotivasi daripada materi yang tidak otentik. Namun di sisi lain, materi otentik dianggap terlalu sulit bagi siswa dengan tingkat pemahaman yang rendah sehingga guru perlu menghabiskan lebih banyak waktu untuk menerapkannya. Pada akhirnya, dalam mengajarkan kemampuan mendengarkan bagi para siswa, guru perlu menyeleksi materi yang sesuai untuk memenuhi tingkat dan latar belakang pengetahuan siswa serta yang paling penting harus sesuai dengan silabus dan tujuan pengajaran. Kata kunci: Materi Otentik, Kelebihan, Kekurangan, Pemahaman Mendengarkan